Safety Studies on Intravenous Administration of Oncolytic Recombinant Vesicular Stomatitis Virus in Purpose-Bred Beagle Dogs - LeBlanc, Amy K. (Mary Ann Liebert, Inc., 2013)
VSV-IFNβ-NIS is a novel recombinant oncolytic vesicular stomatitis virus (VSV) with documented efficacy and safety in preclinical murine models of cancer. To facilitate clinical translation of this promising oncolytic therapy in patients with disseminated cancer, we are utilizing a comparative oncology approach to gather data describing the safety and efficacy of systemic VSV-IFNβ-NIS administration in dogs with naturally occurring cancer. In support of this, we executed a dose-escalation study in purpose-bred dogs to determine the maximum tolerated dose (MTD) of systemic VSV-hIFNβ-NIS, characterize the adverse event profile, and describe routes and duration of viral shedding in healthy, immune-competent dogs. The data indicate that an intravenous dose of 10(10) TCID(50) is well tolerated in dogs. Expected adverse events were mild to moderate fever, self-limiting nausea and vomiting, lymphopenia, and oral mucosal lesions. Unexpected adverse events included prolongation of partial thromboplastin time, development of bacterial urinary tract infection, and scrotal dermatitis, and in one dog receiving 10(11) TCID(50) (10×the MTD), the development of severe hepatotoxicity and symptoms of shock leading to euthanasia. Viral shedding data indicate that detectable viral genome in blood diminishes rapidly with anti-VSV neutralizing antibodies detectable in blood as early as day 5 postintravenous virus administration. While low levels of viral genome copies were detectable in plasma, urine, and buccal swabs of dogs treated at the MTD, no infectious virus was detectable in plasma, urine, or buccal swabs at any of the doses tested. These studies confirm that VSV can be safely administered systemically in dogs, justifying the use of oncolytic VSV as a novel therapy for the treatment of canine cancer.